2012
DOI: 10.1111/j.1365-2230.2012.04438.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-immunoglobulin E in the treatment of refractory atopic dermatitis

Abstract: Atopic dermatitis (AD) is a chronic and relapsing inflammatory skin disease affecting > 10% of children and 1-3% of adults, and can cause significant morbidity. The incidence of AD seems to be increasing. Omalizumab, a monoclonal antibody, has recently been suggested as a potential new systemic treatment for patients with recalcitrant AD with elevated IgE levels, based on its efficacy in treating asthma and allergic rhinitis. We report a study of 10 patients with AD (aged 19-35 years) who received anti-IgE tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 12 publications
3
19
0
1
Order By: Relevance
“…142 However, its efficacy in patients with AD is controversial despite its ability to displace FcεRI on target cells. [143][144][145][146] This again supports the argument against IgE as a key driver of AD. Moreover, treatment of patients with severe AD with cyclosporine resulted in clearance of disease despite unchanged serum IgE levels.…”
Section: Defining Ad Phenotypessupporting
confidence: 71%
“…142 However, its efficacy in patients with AD is controversial despite its ability to displace FcεRI on target cells. [143][144][145][146] This again supports the argument against IgE as a key driver of AD. Moreover, treatment of patients with severe AD with cyclosporine resulted in clearance of disease despite unchanged serum IgE levels.…”
Section: Defining Ad Phenotypessupporting
confidence: 71%
“…Although we did not detect increased protein expression of the high affinity IgE receptor (FcεRI) in lesional extrinsic AD skin, its increased expression, previously noted on IDECs by flow cytometry, 3,54,55 might provide a molecular target for IgE binding that potentially influences more complex immunological circuits in the skin. Although a few reports showed inconclusive effects of anti IgE targeting, 5658 the benefit from such an intervention still needs to be determined, particularly for extrinsic AD.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, more significant results in limiting AD skin symptoms have been reported in patients with concomitant AD and bronchial asthma by small case series involving almost 40 subjects [120124]. For example, Kim et al reported that 7/10 (70%) of patients with AD who received omalizumab for persistent asthma experienced improvement in SCORAD scores; however, no placebo group was included in the study [123]. Moreover, a prospective analysis including 21 patients (14–64 years old) with moderate-to-severe persistent allergic asthma and AD showed a statistically significant clinical improvement of AD in all patients [124].…”
Section: Methodsmentioning
confidence: 99%